Development of predictive preservative model for shelf life parameters of beef using response surface methodology. (October 2016) - Chandra Mohan, C.; Rakhavan, K.R.; Radha Krishnan, K.; Babuskin, S.; Sudharsan, K.; Azhagu Saravana Babu, P.; Sukumar, M.
Abstract: The main aim of this study was to evaluate the effect of spice fused edible films on shelf life parameters of beef meat. Effects of spice fused edible film on pH, color, lipid oxidation and microbial parameters of beef meat were analyzed. Control of lipid oxidation and microbial spoilage were observed in edible film wrapped beef meat. Shelf life of edible film wrapped beef meat was estimated to be 22 days for storage at 10 °C and 32 days for storage in 4 °C. Response surface methodology was found to be a suitable tool for constructing a predictive model for shelf life parameters of beef meat. Correlation coefficient (R 2 ) scores for individual shelf life parameters of edible film wrapped beef samples were estimated to be more than 0.80. Thus, constructed polynomial equation models were found to be fit for prediction of shelf life parameters. Graphical abstract: Highlights: Effect of clove and cinnamon assimilated edible films on the shelf life of beef was analyzed. Spice fused edible films reduced the lipid and protein oxidations of beef meat. Shelf life of edible film wrapped beef meat was estimated to be 22 days in 10 °C and 32 days in 4 °C storage. RSM was found to be a suitable tool for predictive modeling of shelf life parameters of beef meat.